Tracing Sapiential traditions in ancient Judaism - Najman, Hindy.; Rey, Jean-Sébastien.; Tigchelaar, Eibert J. C. (Supplements to the Journal for the Study of Judaism, 2016)
This volume is intended to problematize and challenge current conceptions of the category of "Wisdom" and to reconsider the scope, breadth and Nachleben of ancient Jewish sapiential traditions. It considers the formal features and conceptual underpinnings of wisdom throughout the corpus of the Hebrew Bible, the Dead Sea Scrolls, Hellenistic Jewish texts, Rabbinic texts, and the Cairo Geniza. It also situates ancient Jewish Wisdom in its Near Eastern context, as well as in the context of Hellenistic conceptions of the Sage.